Gottfried Thomasius’s Conception of a Doctrinal Development - Lee, James Ambrose (Zeitschrift für neuere Theologiegeschichte, 2025)
This paper explores Gottfried Thomasius’s impact on nineteenth-century dogmatic development, with a particular focus on his pivotal work, Die Christliche Dogmengeschichte . By comparing Thomasius’s theological viewpoints with those of his contemporaries, such as Ferdinand Christian Baur, the study underscores Thomasius’s unique contributions to Christian doctrine. Key themes include his engagement with the Erlangen School’s emphasis on experiential faith and organicism. The paper places Thomasius within the wider context of the era’s theological debates, highlighting his divergence from other prominent theological figures of the nineteenth century.